2019
DOI: 10.1021/acs.jpcc.8b10797
|View full text |Cite
|
Sign up to set email alerts
|

GaP–ZnS Multilayer Films: Visible-Light Photoelectrodes by Interface Engineering

Abstract: In the field of solar water splitting, searching for and modifying bulk compositions have been the conventional approaches to enhancing visible-light activity. In this work, manipulation of heterointerfaces in ZnS−GaP multilayer films is demonstrated as a successful alternative approach to achieving visible-light-active photoelectrodes. The photocurrent measured under visible light increases with the increasing number of interfaces for ZnS−GaP multilayer films with the same total thickness, indicating it to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…The solid solution was achieved by sequential deposition of ZnS and GaP layers using the growth parameters summarized in Table . The number of pulses applied to each target are the smallest possible that can give a ratio of ZnS:GaP consistent with our previous work (i.e., 3 and 2 for ZnS and GaP, respectively), to ensure sub-monolayer deposition and hence intimate mixing of ZnS and GaP. For comparison, a multilayered film with 10 ZnS-GaP interfaces, multilayered ZnS-GaP (Z/G-ML), was also deposited.…”
Section: Experimental Sectionmentioning
confidence: 63%
See 3 more Smart Citations
“…The solid solution was achieved by sequential deposition of ZnS and GaP layers using the growth parameters summarized in Table . The number of pulses applied to each target are the smallest possible that can give a ratio of ZnS:GaP consistent with our previous work (i.e., 3 and 2 for ZnS and GaP, respectively), to ensure sub-monolayer deposition and hence intimate mixing of ZnS and GaP. For comparison, a multilayered film with 10 ZnS-GaP interfaces, multilayered ZnS-GaP (Z/G-ML), was also deposited.…”
Section: Experimental Sectionmentioning
confidence: 63%
“…With this overarching concept, the authors demonstrated ZnS-GaP multilayered thin films, where intentionally induced bonding between ZnS and GaP layers remarkably improved photoactivity and its effect scaled commensurately with the number of ZnS-GaP interfaces . A follow-up report showed that interdiffusion at the ZnS-GaP interfaces plays a significant role .…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…1) suggests that for (ZnS) 1-x (GaP) x compositions where x ≤ 0.75, the band gap is direct and we predict that compositions with x = 0.25, 0.5 and 0.75 are promising photocatalysts for the production of hydrogen from water under solar radiation due to their band gaps and the positions of the bands relative to vacuum. The potential for achieving visible-light activity with the ZnS-GaP system due to control of local bonding environments has been confirmed in experimental work [99].…”
Section: Electronic Propertiesmentioning
confidence: 80%